Implementation of the Sidogiri Qur'an Method in Improving the Fast Way of Reading the Qur'an at the Zainul Anwar Islamic Boarding School - Siti Mutmainah; Zakiyah BZ (al-Afkar, Journal For Islamic Studies, 2025)
This research explains the implementation of the Sidogiri Qur'an Method (MQS) in improving the fast way of reading the Al-Qur'an at the Zainul Anwar Islamic Boarding School. The Sidogiri Qur'anic method is an integrated approach to learning the Koran which has received widespread attention in the world of Islamic education. The Zainul Anwar Islamic boarding school in Alassumur Kulon utilizes the application of reading the Koran using the Sidogiri Qur'an method which was pioneered by a Salaf Islamic boarding school located in Pasuruan with the name "Sidogiri Islamic boarding school". The type of research used in this research is qualitative research with a case study type. The data collection techniques used in this research include three methods, namely, observation, interviews and documentation. The research objectives of this article are as follows: First, Implementation of the Sidogiri Qur'an method in improving how to quickly read the Qur'an. second, What are the steps for learning the Sidogiri Qur'an method at the Zainul Anwar Islamic boarding school. third, What are the supporting and inhibiting factors in learning the Sidogiri Qur'anic method at the Zainul Anwar Islamic boarding school. The results of this research confirm that learning the Koran by applying the Sidogiri Qur'an method at the Zainul Anwar Islamic boarding school is on target in accelerating the fluency of students so that they can read the Koran quickly and accurately, including the pronunciation of the letters and the recitation. The implementation of learning the Sidogiri Qur'ani method at the Zainul Anwar Islamic boarding school is carried out in accordance with the Sidogiri Qur'an method guidebook. This method uses two learning systems, including pure classical reading and classical listening reading. There are weaknesses in implementing the Sidgiri Qur'ani method at the Zainul Anwar Islamic boarding school, such as student delays and short time. Meanwhile, the advantages of using the Sidogiri Qur'an method are that it is taught simply, practically, does not add material before the students are completely fluent, is always alert, and reprimands the students if they read the wrong reading.